2022
DOI: 10.1039/d2fo00169a
|View full text |Cite
|
Sign up to set email alerts
|

Co-delivery of EGCG and lycopene via a pickering double emulsion induced synergistic hypolipidemic effect

Abstract: The concept of “synergy” and its applications has rapidly increased in the food industry as a practical strategy to preserve and improve health-promoting effects of the functional ingredients. In this...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…Similarly, Sugiura et al reported that combined treatment with EGCG and caffeine (2:1) had overall stronger inhibitory effects on fat accumulation in mice than either alone [ 96 ]. In addition, a recent study reported that the combination of hydrophilic EGCG and lipophilic lycopene synergistically reduced TG and TC levels in serum and liver [ 77 ].…”
Section: Synergistic Hypolipidemic Effects Between Different Categori...mentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, Sugiura et al reported that combined treatment with EGCG and caffeine (2:1) had overall stronger inhibitory effects on fat accumulation in mice than either alone [ 96 ]. In addition, a recent study reported that the combination of hydrophilic EGCG and lipophilic lycopene synergistically reduced TG and TC levels in serum and liver [ 77 ].…”
Section: Synergistic Hypolipidemic Effects Between Different Categori...mentioning
confidence: 99%
“…It has also been reported that the combination of catechins and caffeine can inhibit fat accumulation by suppressing fatty acid synthesis and up-regulating enzymatic activities involved in β-oxidation of fatty acid in the liver, but the combination of EGCG and caffeine did not show the same effect [ 96 ]. In addition, Wang et al demonstrated that the combination of EGCG and lycopene could synergistically lower lipids through different pathways, including HMGCR, LDLR, PPAR, and AMPK at both mRNA and protein levels, and the synergistic hypolipidemic effects could be achieved mainly through the activation of the AMPK pathway [ 77 ].…”
Section: The Synergistic Hypolipidemic Mechanismsmentioning
confidence: 99%
“…This makes DEs a promising co-delivery system for the controlled release of both hydrophilic and hydrophobic bioactive compounds. Over the past few years, numerous hydrophilic and lipophilic bioactive compounds have been simultaneously encapsulated in DEs, including catechin/curcumin [3], EGCG/lycopene [4], EGCG/quercetin [2], vi-tamin C/xanthoxylin [5], phycocyanin/astaxanthin [6], vitamin B12/Cydia pomonella granulovirus (CpGV) [7], and rivoflavin/β-carotene [8].…”
Section: Introductionmentioning
confidence: 99%